Profile of Gut Microbiota of Adults with Diabetes Mellitus Type 1: A Systematic Review - Moreira, Larissa A. A.; da Paz Lima, Larissa; de Oliveira Falcão, Maíra A.; Rosado, Eliane Lopes (Current Diabetes Reviews, 2023)
Background: Type 1 diabetes mellitus (T1DM) is a chronic disease of clinical importance, whose prevalence has increased in Brazil and worldwide. Among the possible factors involved in the genesis and control of the disease, the intestinal microbiota (IM) deserves to be highlighted, but studies that report differences between the IM of patients with T1DM and those who are healthy are still contradictory and scarce. Objective: The objective of this paper was to evaluate the IM profile of T1DM and healthy patients, in order to verify possible differences and to evaluate the possibility of the influence of IM on glycemic control in T1DM. Methods: Of the 2716 articles found, nine were included in this review, and all of which were randomized, observational, cross-sectional, cohort and case-control studies that characterized the composition of IM in adults with T1DM and healthy adults. Results: Studies are very diverse, which makes it difficult to associate the IM profile with T1DM etiology and control, however it was found that there was a prevalence of the phylum Firmicutes in the IM of individuals with T1DM and that there was no significant difference in the relative abundance of Bacteroidetes in both populations. Conclusion: It was also possible to identify an inverse relationship of the genus Bifidobacterium and a positive relationship of the genera Bacteroidetes and Prevotella with the concentration ofglycated hemoglobin. More studies are needed to contemplate the characterization of IM in healthy and T1DM individuals.
Keywords: intestinal microbiome